Soil-lubricant-structure interface mechanics for microtunnelling - Phillips, B (2023)
Pipe-jacking is a trenchless underground construction technique commonly used to create conduits for conveying services such as electrical cables, gas, sewerage, or water pipes whilst keeping surface disruption to a minimum. The installation process consists of a tunnel boring machine (TBM) undertaking controlled excavation at the front of a string of pipes, whilst thrust is applied from a jacking frame located at the rear of the string. As the jacking frame advances the machine and pipe string, lubricant (typically comprising Bentonite clay) is simultaneously injected into an overcut between the pipes and soil formed by the TBM . This process is periodically paused whilst pipes are added and for planned or unplanned stoppages. Currently, there is no commonly accepted model for the behaviour of the soil-lubricant-structure (SLS) interface around these tunnel pipes during advances and stoppages, which results in excessive conservatism in the design stage.